Infection prevention preparedness and practices for female sterilization services within primary care facilities in Northern India - Abhishek Kumar; Abhishek Gautam; Arnab Dey; Ruhi Saith; Uttamacharya; Pranita Achyut; Vandana Gautam; Dinesh Agarwal; Amit Chakraverty; Arupendra Mozumdar; Kumudha Aruldas; Ravi Verma; et al. (BMC, 2019)
Abstract Background In 2014, 16 women died following female sterilization operations in Bilaspur, a district in central India. In addition to those 16 deaths, 70 women were hospitalized for critical conditions (Sharma, Lancet 384,2014). Although the government of India's guidelines for female sterilization mandate infection prevention practices, little is known about the extent of infection prevention preparedness and practice during sterilization procedures that are part of the country's primary health care services. This study assesses facility readiness for infection prevention and adherence to infection prevention practices during female sterilization procedures in rural northern India. Method The data for this study were collected in 2016-2017 as part of a family planning quality of care survey in selected public health facilities in Bihar (n = 100), and public (n = 120) and private health facilities (n = 97) in Uttar Pradesh. Descriptive analysis examined the extent of facility readiness for infection prevention (availability of handwashing facilities, new or sterilized gloves, antiseptic lotion, and equipment for sterilization). Correlation and multivariate statistical methods were used to examine the role of facility readiness and provider behaviors on infection prevention practices during female sterilization. Result Across the three health sectors, 62% of facilities featured all four infection prevention components. Sterilized equipment was lacking in all three health sectors. In facilities with all four components, provider adherence to infection prevention practices occurred in only 68% of female sterilization procedures. In Bihar, 76% of public health facilities evinced all four components of infection prevention, and in those facilities provider's adherence to infection prevention practices was almost universal. In Uttar Pradesh, where only 55% of public health facilities had all four components, provider adherence to infection prevention practices occurred in only 43% of female sterilization procedures. Conclusion The findings suggest that facility preparedness for infection prevention does play an important role in provider adherence to infection prevention practices. This phenomenon is not universal, however. Not all doctors from facilities prepared for infection prevention adhere to the practices, highlighting the need to change provider attitudes. Unprepared facilities need to procure required equipment and supplies to ensure the universal practice of infection prevention.